Direct determination of the absolute configuration of a cyclic thiolsulfinate by VCD spectroscopy - Holmén, Anders; Oxelbark, Joakim; Allenmark, Stig (Tetrahedron: asymmetry, 2003)
Experimental and calculated vibrational circular dichroism (VCD) spectra of the enantiomers of the conformationally rigid thiolsulfinate, naphtho[1,8- cd]-1,2-dithiole 1-oxide 1, obtained by chromatographic resolution of the racemate, were in excellent agreement, showing a (+)-( S)- 1/(−)-( R)- 1 relationship. Graphic